Concurrent Hydrocephalus and Ulcerative Colitis: Exploring the Role of IL18: A Case Report - Nesreen Khallat; Ranim Mira (AlQalam Journal of Medical and Applied Sciences, 2024)
The coexistence of fetal hydrocephalus (HC) and ulcerative colitis (UC) within a single patient is exceptionally rare. This paper presents the case of a 4-year-old girl initially diagnosed with congenital hydrocephalus via in-utero ultrasonography at 20 weeks of gestation. Subsequent ventriculoperitoneal (VP) shunt placement was performed, and 3 years later, the patient was histologically and serologically diagnosed with ulcerative colitis. The synchronization of these distinct medical events in the same individual, particularly the interval between the treatments, represents an unprecedented occurrence not previously documented. The report details the patient’s recent presentation of recurrent bloody diarrhea and failure to thrive, which was effectively managed with oral prednisolone and sulfasalazine. Notably, the simultaneous manifestation of these conditions prompts consideration of potential contributing factors, including genetic markers such as interleukin 18 (IL 18), which have been linked to both disorders in existing literature. This case underscores the need for further research to elucidate the genetic and pathological markers, as well as predictors, which may underlie the concurrent occurrence of hydrocephalus and ulcerative colitis. Understanding these complexities could offer valuable insights into the intricate interplay of genetic and environmental factors in the development of such unique medical co-morbidities. يعد التعايش بين استسقاء الرأس الجنيني والتهاب القولون التقرحي داخل مريض واحد أمرًا نادرًا للغاية. تعرض هذه الورقة حالة فتاة تبلغ من العمر 4 سنوات تم تشخيص إصابتها باستسقاء الرأس الخلقي في البداية عن طريق التصوير بالموجات فوق الصوتية داخل الرحم في الأسبوع 20 من الحمل. تم إجراء تحويلة البطين الصفاقي اللاحقة، وبعد 3 سنوات، تم تشخيص المريض تشريحيًا ومصليًا بأنه مصاب بالتهاب القولون التقرحي. إن تزامن هذه الأحداث الطبية المتميزة في نفس الشخص، وخاصة الفترة الفاصلة بين العلاجات، يمثل حدثًا غير مسبوق لم يتم توثيقه من قبل. ويورد التقرير تفاصيل معاناة المريض الأخيرة من الإسهال الدموي المتكرر والفشل في النمو، والتي تمت إدارتها بفعالية باستخدام البريدنيزولون والسلفاسالازين عن طريق الفم. ومن الجدير بالذكر أن المظهر المتزامن لهذه الحالات يدفع إلى النظر في العوامل المساهمة المحتملة، بما في ذلك العلامات الجينية مثل إنترلوكين 18، والتي تم ربطها بكلا الاضطرابين في الأدبيات الموجودة. تؤكد هذه الحالة على الحاجة إلى مزيد من البحث لتوضيح العلامات الوراثية والمرضية، وكذلك المتنبئات، التي قد تكمن وراء حدوث استسقاء الرأس والتهاب القولون التقرحي بشكل متزامن. إن فهم هذه التعقيدات يمكن أن يقدم رؤى قيمة حول التفاعل المعقد بين العوامل الوراثية والبيئية في تطور مثل هذه الأمراض الطبية الفريدة